The Dual Burden of Child Sexual Abuse: Victim Experiences and Law Implementation Gaps - Fernando, Henky; Larasati, Yuniar Galuh; Abdullah, Irwan; Afriadi, Dedy; Marsaban, Al; Nurasih, Wiji; Morin, Leanne (Universitas Ahmad Dahlan, 2023)
Introduction to The Problem: The experience of sexual abuse in childhood extends beyond detrimental effects on overall well-being, manifesting in the form of adverse treatment during the recovery phase. This critical issue necessitates a thorough reassessment of the effectiveness and dedication in the enforcement of child protection legislation, particularly in how it supports and prioritizes the needs and welfare of these young victims during their recovery journey.Purpose/Objective Study: The primary aim of this research is to delineate the specific characteristics and far-reaching consequences of child sexual abuse, as well as to critically appraise the execution of the child protection laws in terms of the care and treatment provided to the young victims throughout their recovery.Design/Methodology/Approach: Employing a descriptive normative methodology, this study is underpinned by both primary and secondary data sources. Primary data were meticulously collected from online news reports, shedding light on the nature, contributing factors, and multifaceted impacts of child sexual abuse. Complementary secondary data were meticulously compiled from a thorough examination of legislative documents, scholarly books, and pertinent academic articles.Findings: Firstly, the majority of child victims of sexual abuse are under the age of 18, with a significant number of the perpetrators being individuals within the victims’ immediate social circles. Secondly, the ramifications of such abuse extend beyond physical harm, profoundly affecting the psychological well-being and future quality of life of the victims. Thirdly, a notable proportion of these young victims face negative experiences during their recovery, a situation stemming from both societal indifference and the inadequate application of child protection laws. This shortfall in law enforcement fails to sufficiently address and safeguard the rights and well-being of child victims of sexual abuse during their critical period of recovery.Paper Type: Research Article